THE SILENT REMODELER: A CASE OF PAGET’S DISEASE OF THE BONE - Jayakumar, Kanisha Chengi Ramaswamy; Chyun, Ng Sau; Amin, Md Syazwan bin Md (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Paget’s disease of bone (PDB) is a metabolic bone disorder characterized by excessive osteoclastic activity, leading to abnormal bone remodeling. PDB is often underdiagnosed, particularly among Southeast Asians and individuals under 40 years old. We report a rare case of PDB in a 48-year-old Malaysian woman presenting with severe complications. CASE The patient, with a history of hypertension, developed progressive shortness of breath and reduced effort tolerance over a week. She had a five-year history of bilateral hip and knee pain, which led her to change jobs from cashier to babysitter. Over two years, she became increasingly stooped and required a walking stick for support. She also reported bilateral hearing impairment for a week and had unintentional weight loss of 15 kg over two years. There was no family history of bone disorders, trauma, or consanguinity. On examination, she had frontal bossing, interdental spacing, pectus carinatum, bilateral leg bowing and muscle wasting. Biochemical tests showed markedly elevated alkaline phosphatase (1073 U/L) with normal serum calcium and phosphate levels. Serum parathyroid levels were significantly raised (250 pmol/L). She had acute kidney injury (eGFR 27.5 mL/min/1.73 m²) with metabolic acidosis. Imaging revealed bowing of the femur, diploic widening and cotton wool appearance of the skull, severe kyphoscoliosis with possibility of restrictive lung disease, bilateral staghorn calculi and severe pulmonary hypertension with high output cardiac failure. Given the late-stage presentation, she was given IV zoledronic acid (3 mg) and analgesics but succumbed to her illness after eight days of hospitalization. CONCLUSION This case highlights the need for clinicians to be aware of PDB, especially in rare populations. A high index of suspicion in those with characteristic clinical, biochemical and radiological features is essential, as early diagnosis and treatment can improve quality of life and survival.